2020
DOI: 10.15850/amj.v7n4.1955
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Adverse Cutaenous Drug Reactions in Patients with Human Immunodeficiency Virus

Abstract: Background: Adverse cutaneous drug reactions (ACDRs) are common problems in patients during the treatment of various diseases. The clinical feature varies from mild manifestation such as morbilliform, urticaria, and contact dermatitis, to severe manifestation such as Stevens - Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN). Patients infected with the human immunodeficiency virus (HIV) have an increased risk of developing ACDRs due to immune system disruption. This study aimed to describe the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…This is supported by previous studies, which stated that morbilliform eruptions and SJS were found in more than half of HIV/ AIDS patients with CD4+ counts <200 cells/µL. 23 Several drugs were associated with morbilliform eruptions, such as ARTs, trimethoprim-sulfamethoxazole (TMP/SMX), and anti-tuberculosis drugs. The prevalence of morbilliform eruptions due to ART is approximately 10-17%, 7 TMX/SMP approximately 2.6-8%, and anti-tuberculosis drugs approximately 73%.…”
Section: Adverse Cutaneous Drug Reactions (Acdr) Of Hiv/aids Patientssupporting
confidence: 81%
See 1 more Smart Citation
“…This is supported by previous studies, which stated that morbilliform eruptions and SJS were found in more than half of HIV/ AIDS patients with CD4+ counts <200 cells/µL. 23 Several drugs were associated with morbilliform eruptions, such as ARTs, trimethoprim-sulfamethoxazole (TMP/SMX), and anti-tuberculosis drugs. The prevalence of morbilliform eruptions due to ART is approximately 10-17%, 7 TMX/SMP approximately 2.6-8%, and anti-tuberculosis drugs approximately 73%.…”
Section: Adverse Cutaneous Drug Reactions (Acdr) Of Hiv/aids Patientssupporting
confidence: 81%
“…22 A retrospective study by Maharani et al reported that non-nucleoside reverse transcriptase inhibitors (NNRTI) ARTs, namely efavirenz (26.7%) and nevirapine (14.5%) were the most common causes of ACDR. 23 The most common reported incidence of ACDR due to antituberculosis drugs was pyrazinamide, followed by streptomycin, ethambutol, rifampin, and isoniazid. 22…”
Section: Adverse Cutaneous Drug Reactions (Acdr) Of Hiv/aids Patientsmentioning
confidence: 99%
“…In addition, antibiotics are also the drugs most often cause severe ADE in HIV patients according to Maharani et al in their journal. Thus, ADE patients who have a history of drug allergies, especially antibiotics, should be given attention because these antibiotics may be one of the drugs that cause patients to develop ADEs, especially in ADE patients who have comorbidities such as HIV (11,12,13).…”
Section: Discussionmentioning
confidence: 99%